17α-Ethynyl-androst-5-ene-3β,7β,17β-triol (HE3286) Is Neuroprotective and Reduces Motor Impairment and Neuroinflammation in a Murine MPTP Model of Parkinson’s Disease - Ferdinando Nicoletti; Ingrid Philippens; Paolo Fagone; Clarence N. Ahlem; Christopher L. Reading; James M. Frincke; Dominick L. Auci (Parkinson's Disease)
17α-Ethynyl-androst-5-ene-3β,7β,17β-triol (HE3286) is a synthetic androstenetriol in Phase II clinical development for the treatment of inflammatory diseases. HE3286 was evaluated for blood-brain barrier (BBB) permeability in mice, and efficacy in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) murine model of Parkinson’s disease (PD). We found that HE3286 freely penetrated the BBB. HE3286 treatment significantly improved motor function compared to vehicle in the rotarod test (mean 58.2 sec versus 90.9 sec, P<0.0001), and reduced inflammatory mediator gene expression in the brain (inducible nitric oxide synthase, 20%, P=0.002; tumor necrosis factor α, 40%, P=0.038, and interleukin-1β, 33%, P=0.02) measured by reverse-transcriptase polymerase chain reaction. Brain tissue histopathology and immunohistochemistry showed that HE3286 treatment increased the numbers of tyrosine hydroxylase-positive cells by 17% compared to vehicle (P=0.003), and decreased the numbers of damaged neurons by 38% relative to vehicle (P=0.029). L-3,4-dihydroxyphenylalanine (L-DOPA) efficacy was not enhanced by concurrent administration of HE3286. HE3286 administration prior to MPTP did not enhance efficacy. Our data suggest a potential role for HE3286 in PD treatment, and provides incentive for further investigation.